Determination of the caries risk in children under 5 years of age in schools of the northern of Quito, Ecuador - Alex Esteban Carrera; Francisco Carcelén Arce; Ana María Cabezas; María Fernanda Chavez Campuzano; María Jose Jarrin; Alessandro Dourado Loguercio; Ana del Carmen Armas Vega (Kiru)
Objective: Estimated the caries risk of children under 5 years of age in the urban area of the northern sector in Quito, Ecuador. Materials and methods: The sample consisted by 102 pairs; child and parents and / or representatives, who have been accepted a prior informed consent, they were subjected to the management of caries by risk assessment survey (CAMBRA) to determine the risk of presenting caries in their children. We were also done a clinical examination to assess the presence of caries and plaque. The data was compiled in an Excel table and were analyzed in SPSS program. Results: 60.8% of the minor participants belonging to the female gender. CAMBRA survey has a high-risk measure. Meanwhile, the clinical examination determined that the temporal teeth caries index was 4.62 with the presence of a plaque in 86% of the evaluated population. Conclusions: According to the survey, CAMBRA applied, the risk to the presentation of caries is high and is related to the rates of tooth decay and dental plaque detected in the same population.